(untitled) (Sir Salimullah Medical College Journal, 2026)
Background: Chikungunya fever, a mosquito-borne viral infection, is a major public health problem in Bangladesh, often leading to chronic post-viral arthropathy. While hospital-based data exist, little is known about management outcomes in private clinical settings where most patients seek care. The aim a study is to evaluate the clinical challenges, treatment strategies, and outcomes of patients with chikungunya arthropathy managed in private practice in Bangladesh. Methods: A prospective cohort study was conducted from January 2024 to June 2025 in Dhaka with a total of 124 patients. Adults with persistent joint pain (>6 weeks) following laboratory-confirmed chikungunya infection were included. Demographic data, symptom duration, joint involvement, treatment modalities, and functional outcomes (measured by Visual Analogue Scale [VAS] and Modified Health Assessment Questionnaire [MHAQ]) were recorded. Results: A total of 124 patients (mean age 42.6 ± 11.8 years; 68% female) were included. The mean duration of arthralgia at presentation was 10.2 ± 3.7 weeks. The most commonly affected joints were the wrist (76%), ankleand foot (64%), and small joints of the hand (58%). NSAIDs and short courses of corticosteroids were used in 92% and 38% of patients, respectively, while hydroxychloroquine was prescribed in 26%. After 12 weeks of treatment, mean VAS pain scores improved from 7.4 ± 1.2 to 3.1 ± 1.5 (p < 0.001), and MHAQ scores improved from 1.8 ± 0.6 to 0.7 ± 0.3 (p < 0.001). Major challenges included delayed diagnosis, poor drug compliance, and lack of standardized follow-up. Conclusion: Chikungunya arthropathy remains a frequent cause of chronic joint disability in Bangladesh. Sir Salimullah Med Coll J 2025; 33: 113-116